1998
DOI: 10.1002/jlb.64.6.724
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids protect against suppression of T cell responses in a murine model of acute ethanol exposure and thermal injury by regulating IL-6

Abstract: Previous reports by this laboratory demonstrated that acute alcohol exposure combined with a 15% body surface area dorsal scald injury results in significant reductions in delayed-type hypersensitivity (DTH) and splenocyte proliferative responses compared to either insult alone. Previous studies by this lab have also shown that these defects are mediated, in part, by increased production of interleukin-6 (IL-6). Because both alcohol exposure and thermal injury are known to modulate glucocorticoid (CORT) levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 46 publications
3
64
4
Order By: Relevance
“…Although fewer in number, studies by our laboratory and others have clearly shown that injury profoundly impacts the reactivity of the adaptive immune system as well (3,8,12,26,27). The importance of having intact adaptive immunity after injury is demonstrated by key observations by laboratories that studied the septic response to injury.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Although fewer in number, studies by our laboratory and others have clearly shown that injury profoundly impacts the reactivity of the adaptive immune system as well (3,8,12,26,27). The importance of having intact adaptive immunity after injury is demonstrated by key observations by laboratories that studied the septic response to injury.…”
Section: Discussionmentioning
confidence: 83%
“…Eight-to 10-wk-old male BALB/c and BALB/c CD1d knockout (ko) 3 mice used in these studies were obtained from The Jackson Laboratory. NKT cell-deficient BALB/c-J␣281 ko mice were provided by M. Taniguchi (RIKEN, Yokohama, Japan).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported thymic involution caused by a systemic increase of GC during stress (8,35,36). Thermal injury is an extremely stressful event, and the associated response is characterized by a dramatic increase in plasma GC levels, which reach maximal values during the first 48 h postburn injury (11). Several studies have demonstrated a link between GC production following thermal injury and immune dysfunction (3,32).…”
mentioning
confidence: 99%
“…Glucocorticoids are pleiotropic hormones with a wide spectrum of immunomodulatory and anti-inflammatory properties. (3,8,18,21,39,49,50). They function by binding to glucocorticoid receptor, which resides in an inactive form in the cytoplasm of target cells (3,44,49).…”
mentioning
confidence: 99%